Hubungan Literasi Halal dan Keterampilan Berfikir Tingkat Tinggi pada Materi Sistem Pencernaan Manusia Terhadap Pengambilan Keputusan Produk Halal - Rahayu, Bintang Puja; Cahyanto, Tri; Windayani, Neneng (Pusat Kajian Halal Undip, 2023)
The majority of Indonesia's population is Muslim. A good Muslim is a Muslim who follows everything ordered by Allah SWT and leaves all the prohibitions of Allah SWT. One of them is by consuming halal products. The application of halal literacy in education is very influential in improving the quality of faith in Allah SWT and increasing knowledge about halal literacy and making decisions regarding the selection of halal products. Halal literacy can be applied to science material, one of which is about the human digestive system. In addition to halal literacy, higher-order thinking skills are needed in the 21st century. This study aims to determine how halal literacy and higher-order thinking skills in matters of the human digestive system affect consumer decisions about halal products. This study used a quantitative approach involving 31 students from class XI IPS 1 MAN 1 Garut. There are two independent variables in this study, namely halal literacy and higher-order thinking skills, and the dependent variable, namely decision making about halal products. Questionnaires and multiple choice questions were given to students to find out the variables to be studied. By using multiple regression statistics, the results show that there is a relationship between halal literacy and making decisions on halal products, but with higher-level thinking skills there is no relationship with making decisions on halal products. Meanwhile, together between halal literacy and higher order thinking skills there is a relationship with making halal product decisions, namely 51.2% to be precise. Other factors influence 48.8%.